Bioactive molecules extracted from the marine sponge Aplysilla sulfurea and the marine phytoplankton Porosira glacialis - Varmedal, Ingrid (Universitetet i Tromsø, 2009)
Aqueous and organic extracts of the Arctic sponge Aplysilla sulfurea and methanolic extracts from the Arctic phytoplankton Porosira glacialis were fractionated using preparative HPLC into 40 fractions according to the polarity of the components in the extract. The fractions were tested for antibacterial, anticancer and antioxidative activities. After re-chromatography, active fractions were analyzed by mass spectrometry in order to identify components responsible for the confirmed activities. In the organic extracts of the sponge, fractions containing cytotoxic activity were found. Ianthelline, a di-brominated molecule with molecular mass 472.9672 was tentatively identified as the cytotoxic compound. The antibacterial activity of this molecule has previously been published, but the cytotoxicity related to human cancer cell lines has not been reported. The antioxidative activity found in the same fractions was not further investigated due to the likely cytotoxicity of the compound. The semi-aqueous fractions from the pellet of the phytoplankton Porosira glacialis were found to have antioxidative activity. No cytotoxicity was found, and this made the antioxidative components interesting for further investigation by mass spectrometry in order to elucidate the structure. However, the data were complex and not clear, and further investigation will be necessary in order to come to an identification.